British Historical Facts, 1830-1900 - Cook, Chris. author. aut Link
XI, 279 p.
Keywords: British Historical Facts, 1830-1900 comes as an original and pioneering attempt to provide within a single volume a comprehensive yet readily accessible source-book of facts and figures on the Victorian period.